Detection and Quantification of Class I Caries with Laser Fluorescence Technique - Jameel, Rana T.; Jawad, Hussein A. (Iraqi Journal of Laser, 2010)
The objective of the present study is to verify the actual carious lesion depth by laser fluorescence technique using 650 nm CW diode laser in comparison with the histopathological investigation. Five permanent molar teeth were extracted from adult individuals for different reasons (tooth impaction, periodontal diseases, and pulp infections); their ages were ranging from 20-25 years old. Different carious teeth with varying clinical stages of caries progression were examined. An experimental laser fluorescence set-up was built to perform the work regarding in vitro detection and quantification of occlusal dental caries and the determination of its actual clinical carious lesion depth by 650 nm CW diode laser (excitation wavelength (λexcit.) = 669 nm). Five teeth were sent to histopathological examination to confirm the efficacy of laser fluorescence technique for the determination of actual carious lesion depth. The results are leading to the detection of carious lesions for different depths. The deepest carious lesions revealed high fluorescence intensity. Based on these findings; it was concluded that 650 nm CW diode laser (λexcit. = 669 nm 40 mW) is a suitable and a reliable tool for caries diagnosis and depth assessment. Histopathological findings for the estimation of actual carious lesion depth revealed a good correlation with that of laser fluorescence technique.